2017
DOI: 10.13176/11.790
|View full text |Cite
|
Sign up to set email alerts
|

Violence Detection From ECG Signals: A Preliminary Study 

Abstract: This research studied violence detection from less than 6-second ECG signals. Features were calculated based on the Bivariate Empirical Mode Decomposition (BEMD) and the Recurrence Quantification Analysis (RQA) applied to ECG signals from violence simulation in a primary school, involving 12 pupils from two grades. The feature sets were fed to a kNN classifier and tested using 10-fold cross validation and leave-one-subject-out (LOSO) validation in subject-dependent and subject-independent training models respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Once a suspicious event is identified, the primary agent sends signals carrying that suspicious event along with the primary agent's ID and geographical location acquired from GPS to the cloud for further processing. The contribution of detecting violence using human body movements [21,30] and physiological signal [22] fit for this role. Fig.…”
Section: Primary and Secondary Agentsmentioning
confidence: 95%
See 3 more Smart Citations
“…Once a suspicious event is identified, the primary agent sends signals carrying that suspicious event along with the primary agent's ID and geographical location acquired from GPS to the cloud for further processing. The contribution of detecting violence using human body movements [21,30] and physiological signal [22] fit for this role. Fig.…”
Section: Primary and Secondary Agentsmentioning
confidence: 95%
“…EDA [19], EEG [20]. Secondly, the systems use signals measured from the victims directly, for example, their human body movement [21] and ECG signal [22]. Nam, Alghoniemy, and Tewfik pioneered a study on violent scene characterization based on flame and blood detection [16].…”
Section: Research In Violence Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heart rate is one of the commonly measured features in most of the models, and Ferdinando et al [26] found that it could be an indicator of emotional state. Other complex systems involve the use of the electrocardiogram (ECG) to detect an abuse situation [27].…”
Section: Wearable Devices Structured In a Body Area Network (Ban) Envmentioning
confidence: 99%